2018
DOI: 10.1002/jcp.26521
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of interleukin‐6 on Gingival Fibroblasts: Cytokine regulation in periodontitis

Abstract: Periodontitis is a bacterial infectious disease, and many inflammatory cytokines regulate periodontitis pathophysiology through a crosstalk between tissue cells and immune cells. Interleukin (IL)-6 is an important cytokine involved in the regulation of host response to bacterial infection. Human Gingival Fibroblasts (HGFs) are the most abundant cells in gingival connective tissues. Various HGF responses to periodontal pathogens or inflammatory cytokines contribute to the development of periodontitis. Lipopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 81 publications
1
79
0
Order By: Relevance
“…Periodontitis is a chronic infectious disease caused by microorganisms in dental plaque and is characterized by the progressive destruction of periodontal tissues (23). The endotoxins of periodontal-specific pathogens, including Porphyromonas gingivalis, Prevotella intermedia and Actinobacillus actinomycetemura, can cause a large number of inflammatory cytokines to be released in the local and peripheral blood system (24).…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is a chronic infectious disease caused by microorganisms in dental plaque and is characterized by the progressive destruction of periodontal tissues (23). The endotoxins of periodontal-specific pathogens, including Porphyromonas gingivalis, Prevotella intermedia and Actinobacillus actinomycetemura, can cause a large number of inflammatory cytokines to be released in the local and peripheral blood system (24).…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Tominari et al showed that osteoclast differentiation from RANKL‐stimulated mouse bone marrow macrophages is suppressed by compounds inhibiting PGE 2 synthesis by targeting both COX‐2 and mPGES‐1. Both RANKL‐RANK and LPS‐TLR4 signalling pathways are mediated via transcription factor NF‐κB. In response to stimuli, the IKKα/IKKβ/NEMO (IKKs) complex is activated, leading to dissociation of IκBα/NF‐κB complex, and subsequently to nuclear translocation of NF‐κB .…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that IL-1β-expressed inflammatory macrophages produce amyloid β (the main component of the hall marker in the brain of AD patients) in the gingival tissues of the patients with periodontitis as well as in the liver of mice after chronic systemic P. gingivalis infection, indicating that inflammatory macrophages in periodontitis may contribute to neurodegenerative diseases such as AD [34]. IL-6 triggers the generation of vascular endothelial growth factor (VEGF) and MMP-1, making great contribution to the development of periodontitis [35] and synergic effects of IL-1β and IL-6 upregulate MMPs, Evidence-Based Complementary and Alternative Medicine contributing to the tissue destruction in periodontitis by collagen degradation and bone resorption [36]. It is noted that chemical ablation of macrophages in mice prevents the P. gingivalis-induced alveolar bone resorption, demonstrating important roles for macrophages during periodontitis [37].…”
Section: Macrophages In Periodontitismentioning
confidence: 99%